Vascular tumors and developmental malformations : pathogenic mechanisms and molecular diagnosis - North, Paula E.; Sander, Tara (Molecular and translational medicine., 2016)
This book comprehensively covers the classification, histopathology, pathogenesis, and molecular diagnosis of vascular tumors and malformations, correlating these with current approaches to clinical management. It offers a new multidisciplinary resource for clinicians, pathologists, molecular diagnosticians, and scientists in the field of vascular medicine and biology, fostering cross-cutting collaboration in clinical practice and research. Fundamental background information on vascular tumors and malformation is provided, while also including the most current information available on pathogenic mechanisms underlying this heterogenous group of disorders and the implications for molecular diagnosis and therapeutic intervention. Written by experts in the field, Vascular Tumors and Developmental Malformations: Pathogenic Mechanisms and Molecular Diagnosis provides the medical and scientific community with an essential, practical resource to guide accurate diagnosis, well-targeted therapies, and informed investigation of specific clinicopathological entities within the spectrum of vascular anomalies.